A study on clinical profile and outcome of malrotation of intestine in children - Chandrasekaran, Sankkarabarathi; Shanmugam, Vivek (International Surgery Journal, 2017)
Background: Malrotation is a congenital disorder featured with abnormal positioning of intestine within the peritoneal cavity. Its diagnosis is established within one year of age in most of the cases. The present study was conducted with the aim to analyse in detail the entire clinical profile of malrotation of intestine in children and to analyse the value of imaging in diagnosing suspected cases of malrotation. Methods: This prospective study was carried out during the period from September 2010 to January 2013. 70 patients with suspected malrotation based on clinical symptoms and subsequently proven by surgery were included in the study. The surgery was performed based on the clinical signs and symptoms as well as ultrasound and an upper gastrointestinal contrast study by using barium meal follow through (BMFT). Results: Out of 70 patients in this series, 47 (67.5%) were at the age group of less than one week to one month, 10 (14%) were between one month to one year and 13 (18.5%) were older than year. Male: Female ratio was 4:3. 12 (17%) babies were born to consanguity couple. Bilious vomiting was the most common symptom observed in 61 (87%) patients. After X-ray of abdomen, intussusception was diagnosed in 5 patients, X-ray was suggestive in 35 patients (50%), normal in 16 (23%), double bubble sign noticed in 5 (7%) patients. Out of 70, 51 patients had ultrasound abdomen for malrotation. Among them, 36 patients were noticed with altered SMA/SMV axis, 6 with volvulus, 4 reports were normal and 5 were inconclusive. Conclusions: The incidence of malrotation in symptomatic children can be identified by ultrasound of abdomen whereas in case of asymptomatic children, it was diagnosed initially by using abdominal X-ray and later comfirmed by abdominal ultrasound. Once the diagnosis of malrotation has been established, appropriate surgical approach should be carried out to reduce the risk of mortality in infants and children.